Pain management in surgical disciplines - Mátlová, A; Ševčík, P (Rozhledy v chirurgii, 2024)
Pain is a complicated subjective entity that is difficult to quantify and treat. Individuals learn the concept of pain through their life experience, and a person's concept of pain perception changes. Although pain usually fulfills an adaptive role, it can have ad-verse effects on quality of life - functional, social and psychological balance. Therefore, it is necessary to respect the communication of the individual experiencing and feeling pain, or to monitor the various symptoms of pain. Today, perioperative pain management is part of the comprehensive care of patients undergoing surgery, and is associated with numerous benefits for the patient and society. Currently, there are enough drugs, dosage forms, treatment modalities available, as well as enough literary data, incl. knowledge about the organization of postoperative pain treatment. Comprehensive care begins even before surgery in specialized outpatient clinics with the proper preparation of the patient for anesthesia and surgery. The treatment of postoperative pain itself is similar to the care of a patient after a surgical procedure, a multidisciplinary team task, in which the attending physician, surgeon, anesthetist and nurses of the postoperative department participate in particular. Part of this extensive collaboration are specialized teams for the treatment of acute postoperative pain, which primarily have a conciliatory, educational and organizational role, and help to provide specialized treatment procedures for pain relief. It is necessary for all specialists to combine basic knowledge and their application in practice.
Keywords: lidé; Pain, Postoperative; pain; organization of pain management; management bolesti; multimodal analgesia; Humans; Pain Management; perioperative analgesia; pooperační bolest; Pain